Stilʹ i slovo - Liliâ R. Duskaeva; Vladimir A. Salimovskij (Stylistyka, 2018)
The reorientation of linguistics to the study of the regularities of its functioning in stylistics, manifested in the fact that functional style has been regarded as a type of language in any sphere of human activity, regards language in the aspect of differentiation and modification in the basic speech varieties. It is not by chance that text samples from different areas of communication are used in frequency dictionaries. Understanding style as a way to integrate speech performance first put forward the questions of the compositional-semantic organization of the text, the realization of its categories, constructive principles, and techniques. In functional stylistics studies the two main areas – the use of language and the organization of a speech performance – are analyzed as complementary, but cohesion requires understanding the regularities of the functioning of language units in a text with many objectives, updated in texts of the given sphere. To resolve this problem, it is reasonable to rely on the notion of speech genres, each of which is a sequence of standard cognitive-communicative actions – structural elements acting as an object in the text of spiritual socio-cultural activities. The analysis of these actions has revealed and systematized lexical units in communicative composition of language material (Gasparov 2010). This text-centered study of functioning of lexical and other means is of interest not only for the theory of style (and, more broadly, in speech study), but also to practice learning the language in its functional varieties.